Kajian Perilaku RamahLingkungan Generasi Muda terkait Penggunaan Tumbler Ramah Lingkungan - Adam Saputra, Yulius; Dwi Hayu Agustini, M.Y. (IPB University, 2024)
Green environmental issues and Green awareness have become of interest throughout the world. By tending to use Green products, it has had a positive impact on the environment. In everyday use of Green tumblers as an effort to reduce the use of single-use bottles, can be said to have Green behavior. This research aims to find out how Green a person's behavior is seen from the use of a Green tumbler and whether there are differences between levels of Green and demographic factors including age, gender, highest level of education, and monthly income. This research was conducted on people in Semarang City who often use Green tumblers in their daily lives. The sample in this study was taken using the snowball sampling method and obtained 60 respondents. Snowball sampling was carried out by distributing questionnaires to Green tumbler users and through references from friends, relatives, and family. Data were analyzed using descriptive techniques to describe Green behavior based on respondents' perceptions. Then a Chi-Square test was carried out using IBM SPSS statistics 25. The results showed that most respondents belonged to the Greenest class, indicating a high level of Green behavior, with gender as the only demographic factor that showed a significant difference in the use of Green tumblers.